2019
DOI: 10.1016/j.expneurol.2019.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Translational approach towards determining the role of cerebral autoregulation in outcome after traumatic brain injury

Abstract: Cerebral autoregulation is impaired after traumatic brain injury (TBI), contributing to poor outcome. In the context of the neurovascular unit, cerebral autoregulation contributes to neuronal cell integrity and clinically Glasgow Coma Scale is correlated to intactness of autoregulation after TBI. Cerebral Perfusion Pressure (CPP) is often normalized by use of vasoactive agents to increase mean arterial pressure (MAP) and thereby limit impairment of cerebral autoregulation and neurological deficits. However, cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 79 publications
2
9
0
Order By: Relevance
“…For example, cerebral microcirculation disturbance can aggravate ischemia and hypoxia, decrease ATP synthesis, and destroy blood-brain barrier. In addition, the increase in monoamine neurotransmitters, glutamic acid, nitric oxide, bradykinin, endothelin, and arachidonic acid also participate in the occurrence and development of traumatic brain edema (Li et al, 2015;Kozlov et al, 2017;Treble-Barna et al, 2017;Armstead and Vavilala, 2019;Morris et al, 2019). No matter what the pathogenesis of TBI are, the brain tissue edema and nerve fiber damage will occur, which will cause the FA value to decrease and the MD value to increase in DTI (Hanks et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, cerebral microcirculation disturbance can aggravate ischemia and hypoxia, decrease ATP synthesis, and destroy blood-brain barrier. In addition, the increase in monoamine neurotransmitters, glutamic acid, nitric oxide, bradykinin, endothelin, and arachidonic acid also participate in the occurrence and development of traumatic brain edema (Li et al, 2015;Kozlov et al, 2017;Treble-Barna et al, 2017;Armstead and Vavilala, 2019;Morris et al, 2019). No matter what the pathogenesis of TBI are, the brain tissue edema and nerve fiber damage will occur, which will cause the FA value to decrease and the MD value to increase in DTI (Hanks et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…13 Although early data suggest that dopamine should be considered as a first-line treatment to protect AR and improve outcomes, still further basic research is required to see the associated capillary blood flow changes and neurotoxic changes. 12 The choice between mannitol or hypertonic saline for reducing ICP still eludes us. Both these agents are considered to modulate polymorphonuclear neutrophil (PMN) and endothelial cell (EC) activation.…”
Section: Tr In Tbimentioning
confidence: 99%
“…11 The cerebral effect of vasoactive drugs on the preclinical model of TBI has shown that the choice of drug affects AR and CPP. 12 The elevation of mean arterial pressure (MAP) to improve CPP after TBI is insufficient alone to improve outcomes, and maintenance of AR is also an important factor in determining the final outcome. 13 Although early data suggest that dopamine should be considered as a first-line treatment to protect AR and improve outcomes, still further basic research is required to see the associated capillary blood flow changes and neurotoxic changes.…”
Section: Acute Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral autoregulation maintains normal cerebral blood flow(CBF) across a range of blood pressures to ensure sufficient oxygen and glucose can get to their destinations. Cerebral autoregulation is impaired after TBI causing CBF to decrease, which often leads to poor patient outcomes making this one of the important targets for therapeutic intervention following TBI (Roof and Hall, 2000 ; Jalloh et al, 2015 ; Armstead and Vavilala, 2019 ). It was found that cerebral glucose utilization in some brain regions, including the hippocampus, varied with the phases of the estrus cycle in uninjured, normal cycling female rats compared to male rats (Nehlig et al, 1985 ).…”
Section: Introductionmentioning
confidence: 99%